Efektivitas Model Pembelajaran Adaptif Terhadap Peningkatan Kemampuan Teknik Servis Bawah Bola Voli Siswa Sekolah Dasar - Tri Eva Noviani; Ayi Suherman; Tedi Supriyadi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the effectiveness of the adaptive learning model in improving volleyball bottom service technique skills in SDN Bolang students. This study uses a quantitative approach with a pre-experimental design in the form of a one-group pretest–posttest design. The research subjects amounted to 25 students who were selected using the total sampling technique. The research instrument is in the form of a lower service skill assessment sheet which includes aspects of initial attitude, movement execution, ball contact, and the direction of service results. Data analysis techniques include descriptive analysis, normality tests, and simple linear regression. The results showed an increase in the average score from the pretest by 9.48 to 15.84 in the posttest. The results of the regression test showed that the initial ability had a significant effect on the final ability with a significance value of 0.000 (<0.05) and a regression coefficient of 0.528. In addition, the results of the normality test showed that the posttest data was distributed normally, which indicated an equal distribution of students' abilities after treatment. Based on the results of the study, it can be concluded that the adaptive learning model is effective in improving volleyball bottom service technique skills in SDN Bolang students. This learning model can be used as an alternative to PJOK learning strategies that are innovative and in accordance with the characteristics of elementary school students. Keywords: Adaptive Learning, Bottom Serve, Voll, Elementary School, Motor Skills, Volleyball